Changes in heme oxygenase level during development affect the adult life of Drosophila melanogaster - Bilska, Bernadetta; Damulewicz, Milena; Abaquita, Terence Al L.; Pyza, Elzbieta (Frontiers in Cellular Neuroscience, 2023)
Heme oxygenase (HO) has been shown to control various cellular processes in both mammals and Drosophila melanogaster. Here, we investigated how changes in HO levels in neurons and glial cells during development affect adult flies, by using the TARGET Drosophila system to manipulate the expression of the ho gene. The obtained data showed differences in adult survival, maximum lifespan, climbing, locomotor activity, and sleep, which depended on the level of HO (after ho upregulation or downregulation), the timing of expression (chronic or at specific developmental stages), cell types (neurons or glia), sex (males or females), and age of flies. In addition to ho, the effects of changing the mRNA level of the Drosophila CNC factor gene (NRF2 homolog in mammals and master regulator of HO), were also examined to compare with those observed after changing ho expression. We showed that HO levels in neurons and glia must be maintained at an appropriate physiological level during development to ensure the well-being of adults. We also found that the downregulation of ho in either neurons or glia in the brain is compensated by ho expressed in the retina.